(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2022)
In the last few decades, photography has massively grown in terms of production, circulation and reception methods which led to an alleged limitless burgeoning of images from the day-to-day visual culture. This growth carries a change in the way those images are presented to society, and this has to do with the digitalization of photographic media and the increasing use of several online platforms which encourage an almost immediate posting of such images. Considering that, but at the same time growingly frequent scenario, this article aims at questioning the performative construction of photographic pictures that prompt poetic and political actions because of the interposition of scenes from «the real» and «the virtual» world. To do so, some considerations will be drawn regarding the relationship between photography and digitality from a perspective that looks at their performative power. Secondly, we will go back to the idea that a photographic portrait is considered a practice that can carry representation, disappearances, and human rights. Finally, we will acknowledge possible appearances because of the circulation of said pictures. For that matter, we will analyze the formalpoetic strategies identified in a selection of pictures from the series Where is Santiago Maldonado (2017)